Associations between Maternal Exposure to Bisphenol A or Triclosan and Gestational Hypertension and Preeclampsia: The MIREC Study - Camara, Louopou Rosalie; Arbuckle, Tye Elaine; Trottier, Helen; Fraser, William Donald (American Journal of Perinatology, 2019)
Background Little is known about the association between bisphenol A (BPA) or triclosan (TCS) exposure and hypertension in pregnancy.Objective To investigate potential associations between maternal urinary concentrations of BPA or TCS and gestational hypertension (GH) and preeclampsia.Study Design Among 1,909 pregnant women participating in the maternal-infant research on environmental chemicals (MIREC) study, urinary concentrations of BPA and TCS were measured in the first trimester by liquid chromatography-tandem mass spectrometry using isotope dilution. Blood pressure was measured during each trimester. Multinomial regression was performed to estimate the adjusted odds ratio (aOR) and 95% confidence intervals (CI) for the associations between these phenols and GH and preeclampsia.Results BPA and TCS were not associated with GH or preeclampsia. However, in multiparous women, BPA (0.50–1.30 µg/L) was associated with decreased risk of GH (aOR =0.45; 95%CI: 0.21–0.98) while among nulliparous women, TCS was associated with an increased risk of GH (3.60–32.60 µg/L; aOR = 2.58; 95% CI: 1.09–6.13 and > 32.60 µg/L: aOR = 2.74; 95% CI: 1.15–6.51).Conclusion BPA and TCS urinary concentrations were not associated with GH or preeclampsia; however, our results suggest an association between TCS and GH in nulliparous women. Additional studies are required to confirm our results.
Keywords: BPA; TCS; gestational hypertension; preeclampsia; pregnancy; pregnant woman; phenols; environmental chemicals